2020
DOI: 10.1108/ijhrh-09-2019-0076
|View full text |Cite
|
Sign up to set email alerts
|

Psychological well-being of people living near landfills: preliminary case study in Indonesia

Abstract: Purpose The purpose of this study is to explore the psychological well-being of people living around landfills, which constitutes a preliminary case study localized in Samarinda city, Indonesia. Design/methodology/approach This current study used a descriptive, participatory case study design. For data collection, interviews and parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…Relevant studies have found that Wellbeing and quality of life are linked to a positive attitude, which makes people satis ed and healthy in their lives (Hamka et al 2020). Roy et al (2022) con rmed that the defensive attitude of the people may reduce the severity of land ll exposure, improved that defensive attitude near land ll signi cantly affects residents' health status.…”
Section: Impact Of Observational Variables On Health Degreementioning
confidence: 99%
“…Relevant studies have found that Wellbeing and quality of life are linked to a positive attitude, which makes people satis ed and healthy in their lives (Hamka et al 2020). Roy et al (2022) con rmed that the defensive attitude of the people may reduce the severity of land ll exposure, improved that defensive attitude near land ll signi cantly affects residents' health status.…”
Section: Impact Of Observational Variables On Health Degreementioning
confidence: 99%
“…10 The more a person experiences anxiety, the greater the depression. 12 Anxiety is usually due to the loss of a meaningful life [24][25][26] and does not protect the person from physical and mental illness. 10 This symptom is a complex response pattern characterized by feelings of palpitations, chest tightness, trembling, and fainting.…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…37 Spirituality can potentially reduce depression and anxiety by promoting cognition, behavior, and social interaction, which have been shown to protect and prevent depression. 1,26 Stress is a complex and multifaceted phenomenon that results from physiological, cognitive, and social expressions. 24,32 Psychosocial stressors include separation from parents and friends, relocation, environment change, pandemics and outbreaks.…”
Section: The Direct Effect Role Of Stress and Depressionmentioning
confidence: 99%
See 1 more Smart Citation